Acquired hemangioma of the external nose: a case report - Sahoo, Soumick Ranjan; Pallavi Nayak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Hemangiomas of the nose are very rare lesions.They may be found in both paediatric and adult population.The various modalities of treatment may range from medical management to surgical management.We are reporting a benign vascular lesion near the nasal tip at the soft triangle aesthetic subunit in a 64 year old male which was treated by simple surgical excision using electrocautery and primary closure. Histopathological examination of excised specimen confirmed the diagnosis as hemangioma.